The Effect of Clinically Indicated Liraglutide on Pericoronary Adipose Tissue in Type 2 Diabetic Patients - Irmelin I. A. Biesenbach; Laurits J. Heinsen; Katrine S. Overgaard; Thomas R. Andersen; Søren Auscher; Kenneth Egstrup (Cardiovascular Therapeutics)
Vascular inflammation can be detected in the pericoronary adipose tissue (PCAT) by coronary computed tomography angiography (CCTA) attenuation. Treatment with liraglutide is associated with anti-inflammatory effects and reduces cardiovascular risk in diabetic patients. This study is aimed at examining the effect of clinically indicated liraglutide on PCAT attenuation. Asymptomatic patients with type 2 diabetes mellitus (T2DM) and without known ischemic heart disease underwent clinical examination, blood analysis, and CCTA. The main coronary arteries were outlined and PCAT attenuation was measured on the proximal 40 mm. Patients treated with liraglutide on a clinical indication were compared to patients not receiving liraglutide. The study included 190 patients; 53 (28%) received liraglutide (Lira+) and 137 (72%) did not (Lira-). There were no significant differences in PCAT attenuation between the two groups in either artery. However, PCAT attenuation measured around the left anterior descending artery (LAD) was lower in the Lira+ group after adjustment for age, sex, body mass index, and T2DM duration (b coefficient -2.4, p=0.029). In a population of cardiac asymptomatic T2DM patients, treatment with clinically indicated liraglutide was not associated with differences in PCAT attenuation compared to nonliraglutide treatment in the unadjusted model. An association was seen in the adjusted model for the left anterior descending artery, possibly indicating an anti-inflammatory effect.